THE INFLUENCE OF FATWA FOR SHARIA STOCK MARKET MECHANISM ON INDONESIA CAPITAL MARKET PERFORMANCE USING TSR METHODOLOGY - Hidayat Sofyan* (Perbanas Institute, 2021)
This study aims to analyze and assess how fatwa of DSN-MUI affects the performance of the Indonesian capital market represented by the IHSG variable. In this research the VAR/VECM algorithm has been used to form a model to see the impact of the Fatwa DSN-MUI No.80 represented by dummy variable to capital market performance variable Indonesia which in this case is represented by Composite Stock Price Index. In this study also used proxy and interpolation approach. Proxy is to explore theta value and the interpolation is to overcome the void of volume data Sales of FCI. Using TSR method, it can be seen that the effect change from theta, before the screening process with theta after the screening process is to the variable log price (there is increasing of the influence, approximately 3 times) while the influence of the log-vol variable decreases to almost half after theta experienced screening process.